P72 'First report of liver transplantation in Blau syndrome'. (28th September 2020) - Sinharay, Ricky; McKeown, Lorcán; Phillips, Catriona; Li, Alice; Duckworth, Adam; Hall, Frances; Griffiths, William JH
Abstract : Introduction: Blau syndrome is a rare autosomal dominant inflammatory granulomatous disease caused by mutations in the NOD2 gene, classically presenting in childhood. Hepatic manifestations are recognized including cholestasis and granulomatous liver disease. We describe a novel NOD2 gene mutation c.1471A>C, p.(Met491Leu) in an adult presenting with decompensated granulomatous liver disease, requiring an orthotopic liver transplant, the first reported in this syndrome. Disease recurrence has since occurred and he is awaiting re-transplantation related to septic complications from ischemic cholangiopathy. Furthermore, we appraise the effectiveness of antibody therapies in halting disease progression. Case report: Having originally been treated for juvenile idiopathic arthritis and uveitis since the age of three, our patient remained well until the age of 21 when he presented with cholestatic liver enzyme derangement, ascites and weight loss. Imaging suggested portal hypertension and a liver biopsy revealed epithelioid granulomas with no central necrosis and multinucleate giant cells with peri-venular and peri-portal fibrosis. Chronic liver screen and mycobacterial testing was negative. Around this time his daughter developed polyarthritis, uveitis and hepatosplenomegaly at the age of 4 years. She was diagnosed with Blau syndrome after genetic testing revealed the hitherto unreported pathological variant, c.1471A>C, p.(Met491Leu), in the NOD2 gene. Genetic testing confirmed the presence of the same mutation in her father, consistent with a diagnosis of Blau syndrome. At the age of 31, despite selective immunotherapy he developed cirrhotic complications including recurrent oesophageal bleeding and spontaneous bacterial peritonitis. He was accepted onto the liver transplant waiting list and subsequently received a Donation after Circulatory Death (DCD) graft in March 2019. Progress following transplantation was satisfactory and immunosuppression consisted of Tacrolimus, Azathioprine and Prednisolone. Three months later he was treated for septic complications from ischemic cholangiopathy. Imaging revealed a degree of hepatic artery stenosis and bile duct stricturing, thought to be ischemic in nature. He underwent liver biopsy which showed biliary features as well as focal portal and lobular non-necrotizing granulomatous inflammation identical to that seen in his native liver explant, thus in keeping with disease recurrence in his graft. Following his initial grafting he is awaiting re-transplantation. Review of Antibody Therapies in Blau Syndrome Of 84 Blau patients treated with antibody therapy, 5 hepatic cases responded to anti-TNF therapy, with promising results if instigated before decompensation occurs. Conclusion: We report the first case of liver transplantation for Blau syndrome, in an adult case of Blau syndrome with a novel NOD2 mutation.